أهمية موقع المصنع, أسس تحديده وتأثيراته (نموذج: شركات الغزل والنسيج في سوريا) - نادر, نهاد; زاهر, بسام; عرنوق, غازي عفيف (Latakia University Journal - Economic and Legal Sciences Series, 2019)
أثبت التقدم العلمي في المجال الإداري والتنظيم الصناعي أهمية الانتباه إلى موضوع اختيار الموقع الأنسب عند إقامة المنشآت الصناعية, وأثر ذلك على الإنتاج والنتائج، فظهرت الضرورة الكلية لإعداد الدراسات الوافية لاختيار الموقع الأنسب عند إقامة المنشأة الصناعية، كقرار مصيري طويل الأمد، وقبل أي إجراء تنفيذي آخر. هذا ما دفعنا لبحث هذا الموضوع ، مبينين أهم العوامل والاعتبارات المختلفة التي تؤثر على اختيار الموقع الأنسب، وطرق تقييم هذه العوامل، وخصائص كلٍ من أنواع المواقع المختلفة، معتمدين دراسة ميدانية طبقت على عينة من شركات الغزل والنسيج في سوريا (جبلة وحماه) مستخلصين النتائج، خاتمين بالتوصيات والاقتراحات التي نأمل أن تساهم مع الدراسات السابقة, بالاهتمام بدراسة اختيار الموقع الأنسب لإقامة المنشآت الصناعية. The scientific advance in the fields of administration and industrial organization proved the importance of paying proper attention to the subject of choosing the most suitable location when establishing industrial establishments. The location has its effect on production and results. This shows the necessity of conducting proper studies in order to choose the best location for industrial establishments as a long- term crucial decision prior to any other executive procedure. This paper identifies the different factors and considerations that affect the subject of choosing the best location and the methods of evaluating these factors as well as the properties of each location depending on field studies of a sample from the Spinning and Textile Companies in Syria (Jable and Hama). The paper reaches some conclusions and provides some suggestions and recommendations regarding the choice of the proper location for industrial establishments.